Nutrition and adult neurogenesis in the hippocampus: Does what you eat help you remember? - Melgar-Locatelli, Sonia; de Ceglia, Marialuisa; Mañas-Padilla, M. Carmen; Rodriguez-Pérez, Celia; Castilla-Ortega, Estela; Castro-Zavala, Adriana; Rivera, Patricia (Frontiers in Neuroscience, 2023)
Neurogenesis is a complex process by which neural progenitor cells (NPCs)/neural stem cells (NSCs) proliferate and differentiate into new neurons and other brain cells. In adulthood, the hippocampus is one of the areas with more neurogenesis activity, which is involved in the modulation of both emotional and cognitive hippocampal functions. This complex process is affected by many intrinsic and extrinsic factors, including nutrition. In this regard, preclinical studies performed in rats and mice demonstrate that high fats and/or sugars diets have a negative effect on adult hippocampal neurogenesis (AHN). In contrast, diets enriched with bioactive compounds, such as polyunsaturated fatty acids and polyphenols, as well as intermittent fasting or caloric restriction, can induce AHN. Interestingly, there is also growing evidence demonstrating that offspring AHN can be affected by maternal nutrition in the perinatal period. Therefore, nutritional interventions from early stages and throughout life are a promising perspective to alleviate neurodegenerative diseases by stimulating neurogenesis. The underlying mechanisms by which nutrients and dietary factors affect AHN are still being studied. Interestingly, recent evidence suggests that additional peripheral mediators may be involved. In this sense, the microbiota-gut-brain axis mediates bidirectional communication between the gut and the brain and could act as a link between nutritional factors and AHN. The aim of this mini-review is to summarize, the most recent findings related to the influence of nutrition and diet in the modulation of AHN. The importance of maternal nutrition in the AHN of the offspring and the role of the microbiota-gut-brain axis in the nutrition-neurogenesis relationship have also been included.